Iodide manipulation using zinc additives for efficient perovskite solar minimodules - Md Aslam Uddin; Prem Jyoti Singh Rana; Zhenyi Ni; Guang Yang; Mingze Li; Mengru Wang; Hangyu Gu; Hengkai Zhang; Benjia Dak Dou; Jinsong Huang (Nature Communications, 2024)
Abstract Interstitial iodides are the most critical type of defects in perovskite solar cells that limits efficiency and stability. They can be generated during solution, film, and device processing, further accelerating degradation. Herein, we find that introducing a small amount of a zinc salt- zinc trifluoromethane sulfonate (Zn(OOSCF3)2) in the perovskite solution can control the iodide defects in resultant perovskites ink and films. CF3SOO̶ vigorously suppresses molecular iodine formation in the perovskites by reducing it to iodide. At the same time, zinc cations can precipitate excess iodide by forming a Zn-Amine complex so that the iodide interstitials in the resultant perovskite films can be suppressed. The perovskite films using these additives show improved photoluminescence quantum efficiency and reduce deep trap density, despite zinc cations reducing the perovskite grain size and iodide interstitials. The zinc additives facilitate the formation of more uniform perovskite films on large-area substrates (78-108 cm2) in the blade-coating process. Fabricated minimodules show power conversion efficiencies of 19.60% and 19.21% with aperture areas of 84 and 108 cm2, respectively, as certified by National Renewable Energy Laboratory (NREL), the highest efficiency certified for minimodules of these sizes.